Migrant women's voices : talking about life and work in the UK since 1945 - McDowell, Linda (Bloomsbury Academic, 2016)
"Between 1945 and the new century millions of women, including mothers and migrants, joined the labour force. These changes are brought to life through the stories of migrant women, working in factories and hospitals, banks, care homes, shops and universities over a period of 60 years. Migrant Women's Voices is an autobiography of the post-war period as Britain became a multi-cultural society and waged work the norm for most women. McDowell illustrates the shift in migration patterns as post-imperial migrants to the UK replaced the immediate post-war pattern of migrants from war-torn Europe and who were then themselves joined by migrants from an increasingly diverse range of countries as the 20th century drew to a close."--Bloomsbury Publishing